Truth in virtue of meaning - Russell, Gillian Kay, 1976- (Oxford : Oxford University Press, 2008)
The distinction between analytic and synthetic sentences (the idea that some sentences are true or false just in virtue of what they mean) is a famous focus of philosophical controversy. Gillian Russell reinvigorates the debate with a new defence of the distinction, showing that it is compatible with semantic externalism.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Meaning (Philosophy); Grammar, Comparative and general -- Sentences; Knowledge, Theory of